From Firm-Controlled to Consumer-Contributed: Consumer Co-Production of Personal Media Marketing Communication☆. Issue 2 (May 2014) - Bacile, Todd J.; Ye, Christine; Swilley, Esther
Fueled by the sociocultural shift from firm-controlled to consumer-contributed media, the researchers explore the idea of adapting a co-production strategy from service marketing to marketing communication sent to personal media. Eleven field experiments with firms, along with a structural model tested on survey data, provide empirical evidence supporting a co-production approach applied as a communication strategy in the context of a text message mobile coupon marketing campaign. The results demonstrate a co-produced direct marketing communication strategy that increases attitude toward the communication, purchase intent, and purchase activity, while also acting as a risk-reducing mechanism. Furthermore, perceived customization of the communication interacts strongly with risk perception and marginally with coupon proneness as related to attitude toward the communication when marketers enter the world of consumers' personal media. A push versus pull framework and a co-produced communication framework are put forth to suggest various areas marketers can make available for consumers to co-produce in a marketing communication exchange.